A extrafiscalidade aplicada às energias renováveis : uma análise sob a ótica da gestão e proteção ambiental - Sartori, Paola Mondardo (2018)
The environment and its constant degradation are not recent concerns. The possible forms of environmental preservation are subject of constant debate in media, especially because some of the environmental consequences of our inconsequential actions are already palpable. It is undeniable that this debate also orbits the energy sector, given that the sources currently chosen by the Brazilian government for electric power generation aggressively affect the environment. Brazil, despite having hydroelectric plants as its main source of energy, a renewable source although not completely clean, does not have a significant generation through other clean sources, despite having an exorbitant potential, especially with regard to wind and solar energy. Due to the high potential of this type of electric power generation, which is acquired through an inexhaustible and non-polluting source, and the accelerated population growth, which has a significant increase in energy demand, it is undeniable that this type of power generation should be encouraged by the government. Considering this scenario, this research intended, through a dialectical method, to make a legal-dogmatic parallel between the right to an ecologically balanced environment and the current legislation, in order to verify the existing national programs and incentives, as well as to make a juxtaposition between the national and international scenarios, and, finally, discuss the different possibilities of application of the institute of extrafiscality to renewable sources, with the objective of stimulating more effectively this type of power generation in the national territory. In the course of the research, we verified that the range of available alternatives is vast and the application of the extrafiscality to the energy sector has shown to be an excellent tool in the pursuit of constitutional purposes such as the environmental protection. It remains evident, finally, that in order for us to do justice to the constitutional provision that guarantees to everyone the right to an ecologically balanced environment and grant the State duties of environmental protection and promotion, it is necessary that the government actually assume its role of a Socio-environmental State and, urgently, create new and efficient policies, stimulating the national growth of the renewable energy sector, so that we can reach our true potential and guarantee a decent and possible future for the next generations.